Evoluç\~ao tecnológica da indústria brasileira 2000-2016: Uma abordagem quantitativa - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper seeks the elaboration and application of a quantitative measurement for technology in Brazilian manufacturing during 2000-2016. The results have showed stability of the proposed technological indexes and an intensive technological development of the Brazilian manufacturing during 2000-2016.
Keywords: D57; C67; 330; measurement; technology; Brazilian manufacturing